MEMBUMIKAN PENDIDIKAN NILAI MENGHASILKAN AKHLAKUL KARIMAH - Saiful Bahri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2020)
The world of adolescents faces various problems as a result of advances in science and technology which also have a negative impact on various problems, for example the value of mutual assistance, the value of politeness. affection, mutual respect and others that have been lost in adolescents and even in public life in general, the consequences of this current are very influential on the psychology of the development of adolescents today, actually if we observe together a necessity that must be developed by the government, parents, schools and communities must jointly embrace this lost culture so that they realize that the values ​​of politeness, morals, behavior and others are so important in this case, value education plays an important role. Value education is education that considers objects from a moral and non-moral point of view, which includes aesthetics of assessing objects from the point of view of personal beauty and taste, and ethics that assesses right or wrong in interpersonal relationships, education plays a very important value in the endeavor. to reach a whole human. The value of guidance as an integral part of education can be a powerful tool in warding off negative influences, influences both from within the country and abroad.